GEOLOGI DAERAH TEMBUNI DAN SEKITARNYA KABUPATEN BINTUNI PROVINSI PAPUA BARAT - Eric A. Patandianan; AAngelina M. Randa; Raymond M. Awak (INTAN Jurnal Penelitian Tambang, 2021)
Administratively, the study area is located in Tembuni and surrounding area District of Bintuni Papua Barat Province. Geographically located at coordinates 01 ° 47 '00 "latitude - 01 ° 50' 00" latitude (south latitude) and 133 ° 54 '00 "E - 119 ° 57' 00" (East Longitude). The method used for the study is the collection of field data and geological mapping of the surface by recording at each station, taking rock samples for petrographic analysis is then performed based on the data processing is done. The purpose of this study was to obtain geological information in the form aspect of geomorphology, stratigraphy, structural geology, historical geology and extractive potential in the area of further research conducted geological map-making research areas based on four aspects. The research area is divided into three geomorphological units, namely the denudational geomorphological unit with weak-strong waves (D1), the denudational geomorphological unit with strong waves-hills (D2), and the denudational plains unit (D5). The stratigraphy of the study area is divided into two (2) rock units and one (1) sediment, based on lithostratigraphy in order from oldest to youngest, namely: Mudstone Unit, conglomerate unit, and Alluvium and littoral deposits unit. The structure of the research area only found geological structures that developed in the form of a joint secondary structure. The excavated materials found in the research area are excavated materials in the form of rocks originating from alluvial deposits found along the Mogoi Baru village, which are then used as building materials.